2001
DOI: 10.1126/science.1065412
|View full text |Cite
|
Sign up to set email alerts
|

γ-Secretase Cleavage and Nuclear Localization of ErbB-4 Receptor Tyrosine Kinase

Abstract: ErbB-4 is a transmembrane receptor tyrosine kinase that regulates cell proliferation and differentiation. After binding of its ligand heregulin (HRG) or activation of protein kinase C (PKC) by 12-O-tetradecanoylphorbol-13-acetate (TPA), the ErbB-4 ectodomain is cleaved by a metalloprotease. We now report a subsequent cleavage by gamma-secretase that releases the ErbB-4 intracellular domain from the membrane and facilitates its translocation to the nucleus. gamma-Secretase cleavage was prevented by chemical inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
715
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 804 publications
(750 citation statements)
references
References 16 publications
29
715
1
5
Order By: Relevance
“…As a component of γ-secretase complex, nicastrin is also involved in the recognition and cleavage of a variety of other integral membrane proteins such as Notch, Nectin-1a, E-cadherin and ErbB-4 receptor [26,32,35,50]. There is evidence that peptides generated from these cleavage are capable of modulating functions in the developing as well as the adult brain [10].…”
Section: Discussionmentioning
confidence: 99%
“…As a component of γ-secretase complex, nicastrin is also involved in the recognition and cleavage of a variety of other integral membrane proteins such as Notch, Nectin-1a, E-cadherin and ErbB-4 receptor [26,32,35,50]. There is evidence that peptides generated from these cleavage are capable of modulating functions in the developing as well as the adult brain [10].…”
Section: Discussionmentioning
confidence: 99%
“…The NLS reported in this study is underlined. In the case of ErbB4, the intracellular domain was reported to be present in the nucleus [14,15]. It was recently reported that full-length ErbB2, like EGFR and ErbB3, translocates to the nucleus [12].…”
Section: Tab 3 Comparison Of Identified Nls In the Erbb Familymentioning
confidence: 99%
“…The reported tyrosine kinase receptors include four members of ErbB family [11][12][13][14][15] and other tyrosine kinase receptors like VEGF receptor [16], FGF receptor [17,18] and NGF receptor [19]. However, the four members of ErbB family were translocated in the nucleus in different form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleavage by TACE triggers a second cleavage of ErbB4 involving g-secretase activity (Lee et al, 2002). As a result the intracellular domain (ICD) is released from the cell membrane and translocates to the nucleus where it may function as a transcriptional regulator (Ni et al, 2001;Komuro et al, 2003;Ma¨a¨tta¨et al, 2006;Schlessinger and Lemmon, 2006). Consistent with the hypothesis that ErbB4 isoforms differ in their function in tumorigenesis, the cleavable ErbB4 JM-a CYT-2 isoform, but not its noncleavable counterpart JM-b CYT-2, demonstrates ligand-independent activity and promotes cancer cell growth (Ma¨a¨tta¨et al, 2006).…”
Section: Introductionmentioning
confidence: 99%